Reliability of Non-Destructive Test Approach on Structural Strength Assessment - Lim, Debra Vennesa; bin Ayop, Sallehuddin Shah (Recent Trends in Civil Engineering and Built Environment, 2023)
Complaints regarding structural integrity of an existing concrete building aroused questions and safety concerns on the actual condition of the building. Non-Destructive test approach like Rebound Hammer test and Ultrasonic Pulse Velocity Test were conducted to assess the building’s in-situ compressive strength on 10 locations respectively. 5 core samples (100mm x 100mm) were collected to compare and validate both NDTs’ results. Compressive strength conversion obtained through conversion curve for rebound number ranges from 37.07N/mm2 to 56.90N/mm2. The highest recorded reading for UPV test was 3840m/s, while lowest was 2505m/s. The quality of concrete was classified as good for 8 points, 10 doubtful, and 2 poor. Highest core strength was 32.93N/mm2 and lowest at 15.78N/mm2. This suggested compressive strengths obtained through rebound hammer test via the conversion curved indicated an overestimation behaviour. Using SONREB method, conversion of compressive strength using formulations by showed a nearer value to the core specimen compressive strength with highest R2 at 0.0683. Results using SONREB method showed a more reliable estimation of in-situ compressive strength. However, conventional DT method using core test still outrun the reliability of NDT approach in terms of estimation accuracy of compressive strength of existing concrete.